The Impact of Culture on Female School Leaders' Career: A Study among Selected Public Schools in the East Coast of the UAE - SAEED, ALKAABI (2020)
Women in the East Coast of the UAE are a focal part of educational system since the early days of the country's inception; they have confronted several careers' related barriers that prevented them from gaining senior administrative and leadership roles. Fortunately, the situation has positively emerged. Nevertheless, the problem is that there are still few remaining obstacles (psychological due to culture) that may obstruct their careers' development. This study aimed at investigating and synthesizing the impact of culture on women school leaders’ career, psychological status, and their professional development in the educational system in the East Coast of the UAE. The research design was based on a review of the literature, theories (such as Kanters' (1977) Theory, The Scientific Management School in 1880s-90s, transformational leadership theory (1978- 1985) and the trait theory 1930s 1940s). In addition, data collection was conducted through interviews and detailed questionnaires which were administered on 260 women school leaders’ (respondents) as the study employed the mixed method design to be able to collect qualitative and quantitative data. Data was descriptively analyzed using several statistical tools including but not limited to mean and standard deviation computed to present the responses differences, frequency tables, Cronbach’s alpha and ANOVA. As for the study implications, it is expected to contribute positively to the women improvement in leadership positions and gender balance in UAE community and promote the newly enacted constitution. One limitation was faced during the study is that conducting such studies is unwelcomed by a few leaders from the opposite gender (Men). The researcher main finding was that female leadersin the field of education in the East Coast of UAE are facing certain psychologically related pressures by their local community which may affect their careers due to culture (norms, traditions and habits etc. The researcher concluded that Stereotypical image of women in the society is still a barrier to overcome. In addition to gender inequality and psychological factors related to these two problems. The research recommends that future studies could be implemented with government support and in a wider UAE scale and sectors coverage.